National Biosafety Framework for Tanzania: Regulatory regime on genetically modified organisms - Mugurusi, K.; Mwinjaka, S. (TSAP and ILRI, 2006)
The Office of the Vice President of Tanzania, in collaboration with national stakeholders and the United Nations Environment Programme (UNEP), has developed a National Biosafety Framework (NBF) for the implementation of the Cartagena Protocol on Biosafety. The process involved the establishment of a system of legal, technical and administrative mechanisms to address safety in the field of modern biotechnology in the country. In the process of developing the NBF, stakeholders’ workshops and surveys were conducted in 2003 to ensure public participation. Existing local infrastructure and resources were identified to establish the status of the extent to which Tanzania meets the requirements for safe application of modern biotechnology. There exists a widespread interest in the use of biotechnology among various stakeholder institutions in Tanzania. The majority of these institutions are engaged in second-generation biotechnologies (e.g. tissue culture and fermentation). A minority are dealing in third generation (modern) biotechnology (molecular diagnostics, genotyping and taxonomy). There is, however, no institution engaged in the application of recombinant DNA biotechnology. At national level biotechnology policy is currently absent. The Environmental Management Act 2004 was enacted in February 2005. The Act provides for the legal and institutional framework for sustainable management of the environment. The Act further provides for the regulation of development, handling and use of genetically modified organisms (GMOs) and products thereof. It empowers the minister responsible for environment, in consultation with sector ministries to make regulations, issue guidelines and prescribe measures for the regulation of the development, handling, and use and the importation and exportation of GMOs and their products. It is on the basis of the Environmental Management Act 2004 that the proposed draft Environmental Management (Biosafety) Regulations will be established and made operational by the environment minister. This paper details the National Biosafety Framework in Tanzania and the administrative and decision making structure for GMOs. The Vice President’s Office is the National Biosafety Focal point whereby all applications concerning GMOs should be addressed. The ministries of agriculture and food security, health, water and livestock development are some of the key competent authorities in their mandate. This paper also elaborates on the application procedures for the export or importation of GMOs, inspection and enforcement, public education, awareness and participation, monitoring, challenges and way forward.